2017
DOI: 10.2147/ott.s125589
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of the <em>Ezrin</em> gene and circulating tumor cells in osteosarcoma

Abstract: PurposeThe aim of this study was to investigate the clinical significance of circulating tumor cells (CTCs) in the peripheral blood of an osteosarcoma and the Ezrin gene expressed in CTCs.Patients and methodsCTC enrichment was done with CanPatrol™ CTC enrichment technique in 41 patients with osteosarcoma. The characterization of CTCs was performed using a multiple messenger RNA in situ analysis (MRIA). The expression of the Ezrin gene in CTCs was detected by RNA probe technology. The correlations of CTC counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
(35 reference statements)
2
20
1
Order By: Relevance
“…This suggests that CTCs, particularly M-CTCs, may play a crucial role in the metastasis of osteosarcoma. The results of thisstudy are consistent with those reported by Zhong et al; 17 the CTC counts correlated significantly with the Enneking stage ( P <0.001), and the ratio of M-CTCs correlated with the distant metastases ( P <0.001).…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that CTCs, particularly M-CTCs, may play a crucial role in the metastasis of osteosarcoma. The results of thisstudy are consistent with those reported by Zhong et al; 17 the CTC counts correlated significantly with the Enneking stage ( P <0.001), and the ratio of M-CTCs correlated with the distant metastases ( P <0.001).…”
Section: Discussionsupporting
confidence: 93%
“…miR-183-5p is critical in various types of tumor, including hepatocellular carcinoma, osteosarcoma and breast cancer ( 14 ). Ezrin belongs to the ezrin/radixin/moesin family and is a membrane cytoskeletal linker protein functioning in the metastasis of several types of human cancer, including breast cancer, colorectal carcinoma, gastric cancer and serous ovarian carcinoma ( 15 ). In addition, the upregulation of miR-183 represses cell migration and invasion via targeting Ezrin in lung and breast cancer ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…[38,39,40] Ezrin, is a member of the protein family that normally binds the cellular skeleton ERM (ezrin, radixin, and moesin). [41] Ezrin occurs mainly in the inactive form in the cytoplasm, and it transforms to a special active form after the activation with treonin and tirosin phosphorylation. The main biologic function of ezrin is to bind the transmembrane proteins to actin cell skeleton.…”
Section: Treatment Of Osteosarcomamentioning
confidence: 99%
“…Therefore, the ezrin expression plays a significant role in the lung metastasis of the OS cells. [41,42] Receptor Tyrosine Kinases: Ewing sarcoma is a malignant tumor and a member of the round-cell tumors group that is commonly detected between the age of 5 and 25 years and is located in the diaphysis region of the long bones. Ewing sarcoma is the second most commonly detected sarcoma after OS and is detected in the out-of-bone soft tissue location.…”
Section: Treatment Of Osteosarcomamentioning
confidence: 99%